Effective electrical manipulation of a topological antiferromagnet by orbital torques - Zheng, Zhenyi (2024)
The electrical control of the non-trivial topology in Weyl antiferromagnets is of great interest for the development of next-generation spintronic devices. Recent studies suggest that the spin Hall effect can switch the topological antiferromagnetic order. However, the switching efficiency remains relatively low. Here, we demonstrate the effective manipulation of antiferromagnetic order in the Weyl semimetal Mn3Sn using orbital torques originating from either metal Mn or oxide CuOx. Although Mn3Sn can convert orbital current to spin current on its own, we find that inserting a heavy metal layer, such as Pt, of appropriate thickness can effectively reduce the critical switching current density by one order of magnitude. In addition, we show that the memristor-like switching behaviour of Mn3Sn can mimic the potentiation and depression processes of a synapse with high linearity-which may be beneficial for constructing accurate artificial neural networks. Our work paves a way for manipulating the topological antiferromagnetic order and may inspire more high-performance antiferromagnetic functional devices.